Exposure to Phthalate Esters and the Risk of Endometriosis - Kim, Ju Hee (Dev Reprod, 2020)
Endometriosis is a common gynecologic disease, worldwide, whose true prevalence is uncertain because it is a difficult disease to diagnose. Endometriosis is a common cause of chronic pelvic pain, dysmenorrhea, and infertility, and is also associated with ovarian cancer. Although the risk factors for endometriosis are unclear, there is increasing evidence that exposure to environmental contaminants, especially phthalates, could affect the pathogenesis of endometriosis. Phthalates are industrial chemicals, used to make flexible plastics, and are present in numerous common plastic products, including medical devices and materials. Several in vitro studies have suggested a positive association between exposure to phthalate, or phthalate metabolites, and the risk of endometriosis. Since the 2000s, studies based on human plasma and urinary concentrations of various phthalate metabolites have been published, but there are still limitations to our understanding of the pathophysiology of phthalates and endometriosis. This report aims to review the current state of knowledge about a possible role of phthalates in the pathogenesis of endometriosis based on cell culture, animal models, and human data.